Physicochemical, Antioxidant and Mineral Composition of Cascara Beverage Prepared by Cold Brewing - Muriqi, Sali; Červenka, Libor; Česlová, Lenka; Kašpar, Michal; Řezková, Soňa; Husáková, Lenka; Patočka, Jan; Česla, Petr; Velichová, Helena (Food technology and biotechnology, 2025)
RESEARCH BACKGROUND: Cascara, the dried husk of coffee cherries, has attracted attention as a potential beverage due to its unique flavour profile and potential health benefits. Traditionally, cascara is prepared using hot brewing methods. However, recent interest in cold brewing methods has led to research on how temperature affects the functional properties of cascara beverages. EXPERIMENTAL APPROACH: Colour (CIE L*a*b*), total dissolved solids and titratable acidity were determined in cascara beverages prepared at 5, 10, 15 and 20 °C. The concentration of phenols and flavonoids, as well as antioxidant properties were evaluated using spectrophotometric methods. Caffeine, chlorogenic acid and melanoidins were quantified by HPLC. The mineral composition was determined using inductively coupled plasma mass spectrometry (ICP-MS). The results were compared with a hot-brewed cascara beverage. RESULTS AND CONCLUSIONS: Cold brewing resulted in significantly higher concentrations of total phenolic compounds, expressed as gallic acid equivalents (ranging from 309 to 354 mg/L), total flavonoids, expressed as quercetin equivalents (11.8-13.6 mg/L), and caffeine (123-136 mg/L) than the hot-brewed cascara beverage sample (p<0.05). Temperature had a noticeable effect on most variables, although the effect appeared to be random. In particular, concentrations of caffeine (p<0.01) and copper (p<0.001) were highest in beverages prepared at 20 °C and decreased with decreasing brewing temperature. Multivariate analysis showed that minerals (As, Co, Mn, Sn, Mg and Ca), hue and phenolic concentration contributed to the first principal component, which mainly differentiated the hot-brewed sample. Antioxidant-related variables, total titratable acidity and Se contributed most to the second principal component, which facilitated the separation of samples brewed at 5 °C. NOVELTY AND SCIENTIFIC CONTRIBUTION: To our knowledge, this is the first study to suggest that temperature affects the functional properties of cascara beverage produced by the cold brewing method. Experimental evidence supports the existence of a direct proportionality between caffeine and copper concentrations and brewing temperature.
Keywords: caffeine; cold brewing; cascara; temperature effect